PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP LOYALITAS PELANGGAN PADA BENGKEL MOTOR MAKMUR PEKANBARU - putra budi Ansori (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This research was conducted at Makmur Motor Workshops in 2022. This study aims to determine: The effect of Price and Service Quality on customer loyalty at Makmur Motor Workshops. The population in this study are all customers in 2021, totaling 247 customers. Thus the number of samples is rounded up to 71 consumers, after being calculated by the Taro Yamane formula. The sampling technique was carried out by purposive sampling. The results of the analysis are formulated multiple linear regression equations with the equation Y = 5.868 + 0.335X1 + 0.450X2. This shows the value of a (constan) is 5.868, meaning that without the Price (X1) and Service Quality (X2) variables or having a zero value, Customer Loyalty (Y) is worth 5.838. Based on the results of the significant test (t) with the help of SPSS, the partial test results obtained, it can be said that the price and service quality variables partially affect customer loyalty positively and significantly. From the results of the F test it is known that simultaneously the price and service quality variables affect customer loyalty Makmur Motor Workshop Pekanbaru. Furthermore, the value of Adjusted R Square is 0.488. This value can be interpreted that changes in customer loyalty values ​​are influenced by changes in the value of the independent variable price and service quality by 48.8% while 51.2% is determined by other variables that are not in this research model.